Valuation Risk in Mutual Fund Portfolio Disclosure - Chen, Hsiu-Lang (The Review of Asset Pricing Studies, 2022)
Abstract Valuation risk of a security—uncertainty about its fair value—is a subject of considerable concern in the mutual fund industry. If funds report different values for identical securities, investors cannot easily compare their performance. Yet it is not unusual to see identical illiquid stocks, small-cap stocks, stocks with high analyst dispersion, stocks with less analyst coverage, and newly listed stocks valued differently across mutual funds. An equity fund that has positive price dispersion in its portfolio holdings, that performs poorly, that belongs to a fund family with an inclination for aggressive reporting, that holds more stocks subject to stale prices, that holds more pre-IPO firms, or that experiences net outflows will tend to show positive price dispersion again in the next quarter. This behavior is significant in a volatile market. Aggressive reporting helps funds gain in the mutual fund tournament. (JEL G10, G23)